(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
Antineutrophil cytoplasmic antibody–associated vasculitis represents a group of severe systemic autoimmune diseases characterized by inflammation of small- and medium-sized blood vessels, often leading to life-threatening organ damage. Over recent decades, advances in immunosuppressive therapy have significantly improved patient survival and remission rates. However, long-term disease control remains limited by frequent relapses and treatment-related toxicity. This narrative review aims to evaluate the efficacy and safety of current immunosuppressive therapies used in the management of ANCA-associated vasculitis, with particular emphasis on emerging glucocorticoid-sparing strategies. Evidence from randomized controlled trials and observational studies demonstrates that conventional induction regimens combining high-dose glucocorticoids with cyclophosphamide or rituximab achieve high remission rates. Rituximab has emerged as an effective alternative to cyclophosphamide, showing comparable efficacy across different disease subtypes and patient populations. Despite these advances, infectious complications and cumulative glucocorticoid toxicity remain major challenges, contributing substantially to morbidity and mortality during both induction and maintenance therapy. Recent data highlight the potential role of targeted therapies, particularly avacopan, a selective C5a receptor antagonist, in reducing glucocorticoid exposure while maintaining effective disease control. Avacopan-based regimens have been associated with improved safety profiles and enhanced health-related quality of life without an increased risk of serious infections. Overall, optimizing the balance between therapeutic efficacy and safety remains central to improving long-term outcomes in ANCA-associated vasculitis.